Writing the Lives of Fungi at the End of the World. (2nd January 2020) - Harley, Alexis
Abstract: This essay examines how three recent monographs writing the lives of fungi use the co-constitutive entanglements of mycorrhizal fungi and their symbionts in order to bring the contingent, relational conditions of being itself into sharper relief. The Anthropocene demands a heightened awareness of multispecies entanglements, bringing into question the humanist ideal of human agency by turning to the co-constitutive relations of human and nonhuman lives.